Implementation of The Program for Family Development for Toddlers (BKB) in Mentian Village, Prajurit Kulon District, Mojokerto: Implementasi Kebijakan Program Bina Keluarga Balita (BKB) Di Kelurahan Mentikan, Kecamatan Prajurit Kulon, Mojokerto - Gyzzellafora Indyaningtyas; Isnaini Rodiyah (Academia Open, 2022)
This study aims to analyze and describe the implementation of the Bina Keluarga Balita program policy in Mentikan Village, Prajurit Kulon District, Mojokerto. By using qualitative descriptive research methods. The technique of determining the informants is purposive sampling. The technique of collecting data is by observing, interviewing, and documenting as well as analyzing the data by collecting data, reducing data, presenting data and drawing conclusions. The results showed that in the process of implementing the Bina Keluarga Balita (BKB) program policy, from the size and objectives, the implementers already understood the policy standards and targets aimed at developing resilience, empowering families, improving environmental quality. There are still family who are less open minded in the BKB program. The communication between organizations have been going well according to the rules. The characteristics of the implementing agency run according to the organizational structure. The social, economic, and political conditions also influence the implementation of the BKB program policy in Mentikan Village, from an economic point of view, mothers cannot participate in BKB activities due to work demands, and the social aspect of the BKB program can add insight and knowledge of mothers to educate their children. ,as well as in terms of politics so far there has been no change in laws and regulations. The dimension of the implementing tendency goes well, but there are some people who are less open minded. The conclusion of this study is that the implementation of the BKB (Bina Keluarga Balita) program policy in Mentikan Village, PrajuritKulon District, Mojokerto has been going well but there are still people who lack knowledge or understanding of the importance of the BKB program, and socialization is less than optimal due to the difficulty of conditioning the schedule of the students. Working mothers.